Backing outsiders: Selection strategies for discontinuous innovation - Bessant, John; von Stamm, Bettina; Möslein, Kathrin; Neyer, Anne-Katrin (R & D Management, 2010)
A key challenge in managing innovation is to explicitly identify ways to improve an organization's performance with regard to discontinuous innovation. However, discontinuous innovation does not fit the existing 'frame of reference' and hence requires a reframing of the traditional ways of innovating within the organization. More specifically, previous research shows that practices that work well in the context of incremental innovation do not work in the context of discontinuous innovation. Thus, the aim of this paper is to explore innovation practices that enable organizations to select innovation projects, which are 'outside the box' of its prior experience, i.e. are discontinuous in nature. Building on the experience of more than 150 firms across 12 countries, we have identified nine innovation practices for the selection of discontinuous innovation; these can be grouped into three clusters: enable, engage and experience. In sum, we identify that an organization needs to acknowledge that its choice to engage in discontinuous innovation will have consequences for the innovation practices chosen to select which discontinuous projects to carry forward. © 2010 The Authors. Journal compilation © 2010 Blackwell Publishing Lt
WiSo-Import:2015-03-26:510
Keywords: Innovation; Forschungsbericht 2010